Literary Castlings in Bernard Foys tredje rockad. - Oscarson, Christopher (Scandinavian Studies)
Comments on the novel `Bernard Foys tredje rockad,' by Lars Gustafsson. Analysis on the metaphor of castling in chess in the novel's opening; Summary of the novel's three sections; Ontology of the subverted detective story genre in the novel; Examples of involutions in the novel.